Evaluation of the FreeStyle® Libre Flash Glucose Monitoring System in Children and Adolescents with Type 1 Diabetes - Massa, Guy G; Gys, Inge; Op 't Eyndt, Anniek; Bevilacqua, Esmiralda; Wijnands, Anne; Declercq, Peter; Zeevaert, Renate (Hormone research in paediatrics, 2018)
The FreeStyle® Libre Flash Glucose Monitoring System (FGM, Abbott) measures glucose concentrations in the interstitial fluid for up to 14 days. It has been approved for use in children aged > 4 years in January 2016. Experience in children is still limited. We evaluated the accuracy and usability of the FGM in children with type 1 diabetes mellitus (DM). 67 children with type 1 DM (35 girls), aged 4-18 years, were included. Subjects wore a sensor on the back of their upper arm. For the first 14 days, they regularly measured capillary blood glucose (BG) with their usual BG meter (Accu-Chek® Mobile [ACM], Roche [n = 24]; Contour® Next Link [CNL], Bayer [n = 26]; OneTouch® Verio® IQ [OTV], LifeScan [n = 17]) followed by a sensor glucose (SG) scanning. SG readings were compared to BG measurements by consensus error grid (CEG) analysis; the mean difference (MD), the mean relative difference (MRD), the mean absolute difference (MAD), and the mean absolute relative difference (MARD) were calculated. After 14 days, subjects were asked to fill in a questionnaire on the usability of the FGM. 2,626 SG readings were paired with BG results. FGM readings were highly correlated with BG (r = 0.926, p < 0.001). 80.3% of the data pairs were in zone A (= no effect on clinical action) and 18.4% were in zone B (= altered clinical action with little or no effect on the clinical outcome) of the CEG. Overall MD was +7.5 mg/dL; MD varied with the BG meter: ACM +10.4 mg/dL, CNL +14.2 mg/dL, OTV -3.6 mg/dL (p < 0.001). Overall, MARD was 16.7%. We observed a large interindividual variability in the accuracy parameters. MD and MRD were inversely related to BMI (r = -0.261 [p < 0.05]; r = -0.266 [p < 0.05], respectively). MARD was inversely related to age (r = -0.266 [p < 0.05]). Twenty-nine patients (43.3%) reported sensor problems, mainly early detachment of the sensor. Nonetheless, the usability questionnaire indicated high levels of satisfaction. Our results showed a reasonable agreement between the FGM SG readings and capillary BG measurements in children. There was, however, a large interindividual variability. The wearing of the sensor requires special attention. Further studies in children are imperative in order to document the accuracy and safety of the FGM in the paediatric population.